Cervical cytopathological changes in Pap smear test in the city of Santa Cruz do Sul, Rio Grande do Sul, Brazil - Édina K. Fredrich; Jane D. P. Renner (Sociedade Brasileira de Patologia Clínica, 2019)
ABSTRACT Objective: To determine the cytopathologic alterations in women who undergo the Papanicolaou exam by the single health system in a laboratory in the city of Santa Cruz do Sul, Rio Grande do Sul, Brazil. Methodology: Data were collected from cytopathological reports of the year 2015 by the cancer information system. The variables referring to age and cytopathologic alteration were selected. The analyzes were performed by descriptive statistics, including frequency, mean, standard deviation. The associations between the categorical variables were evaluated by the Qui Quadrado test in SPSS software version 22.0. Results: In the year 2015, 2346 women underwent cytopathological examination, where 34.7% were within the limits of normality, 62.6% presented benign cellular alteration, of which 47.5% were inflammatory. Of the alterations, 1.8% were atypical squamous cells of undetermined significance (ASC-US); 0.6% were low-grad squamous intraepithelial lesion (LSIL); 0.2% were atypical squamous cells and it was not possible to exclude high grade squamous intraepithelial lesion (ASC-H); and 0.1% were high-grade intraepithelial lesions (HSIL). Regarding the age of the women, a higher frequency was observed in the age group above 55 years and an average of 46.5 years. Conclusion: The benign cellular alterations were the most frequent, with the prevalence of inflammation. The most common precursor lesions of cervical cancer were ASC-US and LSIL.